How sustainable logistics solutions and technologies have helped Walmart become more efficient - Venkataraman, Ray R. (SAGE Knowledge. Cases., 2017)
This case illustrates the relationship between logistics management and sustainability. The impressive results of Walmart's sustainable logistics solutions show that it is viable to achieve a balance between economic, environmental, and social objectives. For example, by optimizing routing and loads of its trucking fleets with a focus on reducing waste, energy consumption, and carbon emissions, Walmart, in 2015 reported that it had exceeded the greenhouse gas emission goal set in 2010 by 8.2 million metric tons, doubled the fuel efficiency of its fleets since 2005, and saved $1 billion along the way.